1962
DOI: 10.1097/00004032-196212000-00028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diethylenetriaminepentaacetic Acid (DTPA) on Acceleration of Excretion of Actinide Elements

Abstract: This study was set up to determine by whole-body counting the effectiveness of DTPA in hastening the excretion of americium (a) when the drug was given orally as compared to parenteral administration, (b) when treatment was delayed after various periods of time, and (c) when the radioisotope was deposited in the lungs. The experiment was stopped after 50 days. Oral treatment, while not as effective as parenteral treatment, was still surprisingly effective. The drug did significantly lower the body burden of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Assuming that 3 and 4%, respectively, of the labeled surfaces of the bones of adult and growing rats is resorbed daily, the calculated amounts of nuclide remaining in bone agree with the amounts measured by FOREMAN (1962), SEIDEL and VOLF (1972), TAYLOR (1960), andSOWBY (1962), in which DTPA treatments were begun 6 to 14 days after nuclide injection and lasted for 7 to 23 days. In the studies of , .…”
Section: Chelation Of Actinides Deposited In Bonesupporting
confidence: 78%
See 3 more Smart Citations
“…Assuming that 3 and 4%, respectively, of the labeled surfaces of the bones of adult and growing rats is resorbed daily, the calculated amounts of nuclide remaining in bone agree with the amounts measured by FOREMAN (1962), SEIDEL and VOLF (1972), TAYLOR (1960), andSOWBY (1962), in which DTPA treatments were begun 6 to 14 days after nuclide injection and lasted for 7 to 23 days. In the studies of , .…”
Section: Chelation Of Actinides Deposited In Bonesupporting
confidence: 78%
“…At times longer than 1 to 2 days after nuclide injection, any nuclide that is still in the marrow has been deposited in bone, and nuclide initially only loosely bound at bone surfaces has become more firmly fixed. (FOREMAN, 1962;BELYAEV, 1969;SEIDEL and VOLF, 1972;NENOT et al 1971c; Table 30). Delayed DTPA treatment of 241 Am deposited in the bones of 7-week-old rats has been studied by SOWBY and TAYLOR (1960) and D.…”
Section: Chelation Of Actinides Deposited In Bonementioning
confidence: 98%
See 2 more Smart Citations
“…123 This relative solubility makes chelation of 24'Am with diethylenetriaminepentaacetate (DTPA) effective. A number of studies have demonstrated that 241Am can be removed from the body using DTPA or other chelating agents (Co74;L176;NC71;Fo62;Se73;Se75;Ta62;Ta66). DTPA has also been used to treat persons accidentally exposed to 241Am (Ha68: Co76).…”
Section: Introductionmentioning
confidence: 99%